Xuexi Dandongzhan huochang ganbu congshen zuoze ganzhua ganguande zuofeng - Chen Jinghui
'Study the transport yard of Dandong railway station, let cadres set an example by their own conduct with a dare to grasp dare to manage workstyle'.